Implementation of Gusjigang Based Multicultural Counseling at Islamic Religious Higher Education (PTKI) - Farida Ulyani; David Ari Setyawan (Al Hikmah: Journal of Education, 2023)
This research uses a case study approach with the aim of understanding in more depth a unique phenomenon related to the implementation of Gusjigang- based multicultural counseling through the integration of Islamic boarding schools (pesantren) and universities. The pesantren in this case refers to the PRISMA Kudus Student Islamic Boarding School, and the university in question is IAIN Kudus. The research subjects were 7 (seven) West Papuan students who were studying at IAIN Kudus and studying at PRISMA, while the counselor was a BK lecturer at the BKPI Study Program at IAIN Kudus. The counseling process was carried out by integrating the Islamic boarding school system and the education system when a counselor was from a Javanese cultural background and the counselee had a Papuan background. There were four things that needed to be considered, namely (1) paying attention to the client in this case 7 Papuans along with their cultural background. (2) counselors with their cultural background, namely in this case from their culture; (3) the cultural environment in which counseling was carried out, namely in terms of their culture.